Public Service Innovation: "SI N'DUK" Program at the Department of Population and Civil Registration Bojonegoro Regency, Indonesia: Public Service Innovation: "SI N'DUK" Program at the Department of Population and Civil Registration Bojonegoro Regency, Indonesia - Ahmad Suprastiyo, Ahmad Suprastiyo (Advances in Social Sciences Research Journal, 2021)
ABSTRACT This research was conducted at the Department of Population and Civil Registration of Bojonegoro Regency. The purpose of this study was to describe and analyze an innovation in population administration services for the Si N'duk application released by the Department of Population and Civil Registration of Bojonegoro Regency. The focus of this study is to describe the innovation of the Si N'duk population administration service application based on the theory of innovation attributes according to Rogers. The research method used is descriptive research using qualitative data analysis techniques. The results of this study indicate that based on the theory of innovation attributes according to Rogers, most of the population administration service innovations in the Si N'duk application have fulfilled this theory. However, there are still some problems, such as those experienced by the community in the process of uploading population document files, then in terms of the application there is still no application form download feature, there is no notification notification when there is a service application, and application upgrades have not been carried out. In addition there are also problems related to servers and networks. Of course, these shortcomings must be corrected in order to continue to provide the best service innovations for the community. Therefore, from the problems that occur, it is necessary to have a routine performance evaluation that must be carried out by the Population and Civil Registration Office of Bojonegoro Regency so that innovation in population administration services through the Si N'duk application can provide more benefits for the community as service recipients. Keywords: Innovation, Population Administration, Si N'duk Application